Targeted social marketing of PrEP and the stigmatization of black sexual minority men - Calabrese, Sarah K.; Kalwicz, David A.; Dovidio, John F.; Rao, Sharanya; Modrakovic, Djordje X.; Boone, Cheriko A.; Magnus, Manya; Kharfen, Michael; Patel, Viraj V.; Zea, Maria Cecilia (PloS one, 2023)
Disparities in HIV incidence and PrEP uptake suggest a need to prioritize Black sexual minority men (SMM) in PrEP social marketing initiatives. However, images linking Black SMM to HIV and PrEP may inadvertently reinforce stigma. We examined HIV-negative/status-unknown Black SMM’s responses to targeted PrEP advertisements using mixed methods, including an experiment embedded in a longitudinal online survey (Time 1: n = 96; Time 2 [eight weeks]: n = 73) and four focus groups ( n = 18). The full factorial experiment included between-groups and within-subjects comparisons. For between-groups comparisons, each participant was randomly assigned to view one of 12 advertisements, which varied by couple composition (Black SMM couple/Black heterosexual couple/multiple diverse couples/no couples) and campaign ( PrEPare for the Possibilities/PlaySure/PrEP4Love ). We examined couple composition, campaign, and interaction effects on: advertisement judgments (Time 1), PrEP stigma (Time 1), PrEP motivation (Times 1 and 2), and PrEP behavior (Time 2). For within-subjects comparisons, each participant viewed all 12 advertisements, and we examined couple composition, campaign, and interaction effects on advertisement judgments (Time 2). Focus group participants discussed advertising preferences and responded to the same set of advertisements. For between-groups and within-subjects comparisons, we found significant couple composition effects but no or limited campaign and interaction effects on advertisement judgments. Advertisements featuring Black SMM exclusively were judged as more stigmatizing than advertisements without couples. Advertisements with diverse (vs. no) couples were considered more eye-catching and motivating. There were minimal effects of couple composition and campaign on PrEP stigma, motivation, and behavior. Focus group participants corroborated concerns about the potential for PrEP advertisements to be stigmatizing, suggesting advertisements featuring Black SMM exclusively could be alienating and fuel conspiracy theories. Focus group participants generally favored diverse and less sexualized advertisements, particularly for public spaces. Findings collectively highlight the potential for targeted PrEP advertisements to stigmatize Black SMM and support diverse representation.